2008
DOI: 10.1038/emboj.2008.163
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of 4E-BP by LRRK2 affects the maintenance of dopaminergic neurons in Drosophila

Abstract: Dominant mutations in leucine-rich repeat kinase 2 (LRRK2) are the most frequent molecular lesions so far found in Parkinson's disease (PD), an age-dependent neurodegenerative disorder affecting dopaminergic (DA) neuron. The molecular mechanisms by which mutations in LRRK2 cause DA degeneration in PD are not understood. Here, we show that both human LRRK2 and the Drosophila orthologue of LRRK2 phosphorylate eukaryotic initiation factor 4E (eIF4E)-binding protein (4E-BP), a negative regulator of eIF4E-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
536
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(572 citation statements)
references
References 40 publications
26
536
5
Order By: Relevance
“…This pattern of binding is consistent with the patterns observed for other LRRK2 binding proteins, including mitogen activated kinase kinases (MKKs) and c-Jun N-terminal Kinase-interacting proteins (JIP) (10,11); the binding sites for other putative binding proteins such as Fas-associated protein with death domain (FADD), moesin, Rab5, 14-3-3, ArhGef7, and 4E-BP are not known (16,(35)(36)(37)(38)(39) (40,41). LRRK2 also binds to itself and to LRRK1 as homo-and heterodimers (22,23,31,42).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This pattern of binding is consistent with the patterns observed for other LRRK2 binding proteins, including mitogen activated kinase kinases (MKKs) and c-Jun N-terminal Kinase-interacting proteins (JIP) (10,11); the binding sites for other putative binding proteins such as Fas-associated protein with death domain (FADD), moesin, Rab5, 14-3-3, ArhGef7, and 4E-BP are not known (16,(35)(36)(37)(38)(39) (40,41). LRRK2 also binds to itself and to LRRK1 as homo-and heterodimers (22,23,31,42).…”
Section: Discussionmentioning
confidence: 55%
“…LRRK2 kinase activity also does not meet these strict criteria because only the G2019S LRRK2 mutation has been consistently shown to increase kinase activity (36,42,43). Binding of LRRK2 to proteins such as 4E-BP either is not affected by disease-linked mutations or has not been investigated (37). FADD is the only LRRK2 binding protein that show consistent changes in binding (increased) with a panel of multiple disease-linked LRRK2 mutations (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance of various cancers to mTOR inhibitor treatment indicates that other pathways are implicated in 4E-BP1 inactivation (14). Several serine/threonine kinases have been shown to phosphorylate 4E-BP1, such as p38 MAPK, ERK, PIM2, ATM, CDK1, PLK1, LRRK2, GSK3β, and CK1e (15)(16)(17)(18)(19)(20)(21)(22)(23). We recently demonstrated that cyclin-dependent kinase 1 (CDK1) phosphorylates 4E-BP1 at canonical sites T37, T46, S65, and T70 during mitosis and generates a high-molecularweight phospho-isoform called δ-4E-BP1, even in the absence of mTOR activity (24).…”
Section: Merkel Cell Polyomavirusmentioning
confidence: 99%
“…LRRK2-mediated miRNA regulation is exacerbated by these mutations, whereas a kinase-dead LRRK2 mutant does not affect gene repression [43]. The LRRK2 substrate 4E-BP associates with Argonaute 2, a component of the RNA-induced silencing complex (RISC), and this interaction is promoted by I1915T and G2019S mutants of LRRK2, presumably due to increased phosphorylation of 4E-BP1 [45]. Thus, compared to wild type, the phosphomimetic 4E-BP(TE) is more toxic to dopamine neurons and is more effective than wild-type 4E-BP in attenuating let-7 activity in vivo.…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasementioning
confidence: 99%